An impact evaluation framework based on sustainable livelihoods for energy development projects: an application to Ethiopia. (May 2018) - Colombo, Emanuela; Romeo, Francesco; Mattarolo, Lorenzo; Barbieri, Jacopo; Morazzo, Mariano
Abstract: Within the current global challenges, energy plays a key role for the achievement of basic human needs, socio-economic development, environmental protection and global security. At the light of this interconnection, a proper impact evaluation metric able to assess the main effects of energy projects at local level becomes necessary in order to highlight successful strategies. Relying on the Sustainable Livelihoods concept, this study proposes an Impact Evaluation Framework (IEF) to measure project impact as changes of target community's livelihoods. First, the IEF establishes a Capitals-Based Evaluation Hierarchy, taking its rationale from the literature: this first step responds to the needs of providing a standard and harmonized structure applicable to different projects. Secondly, the IEF develops a further Five-Step Procedure to respond to the concurrent need of flexibility and customization of specific projects. The conceptual methodology of the IEF might be used at different stages of project design: as a supportive methodology donors use in their programme of funds allocation or as an instrument experts use to quantitatively support their ex-post project evaluation. In the paper, the IEF is presented in the light of this second application and the procedure applied to a real project in Ethiopia. The set of information obtained with the IEF is compared to the final expert evaluation, commissioned by the donor and performed at the end of the project, showing the usefulness of IEF as a supportive methodology in the evaluation process.